KAJIAN SEMANTIK: ITTIDHAD DALAM PEMAKNAAN AL-QUR’AN SURAH SABA - Chicin Marchella Kolintama (LP2M IAIM Sinjai, 2022)
This study aims to determine the types of antonyms contained in the Qur'an specifically for Surah Saba totaling 54 verses by displaying tables that have several columns containing the verses and their types of antonyms, as well as an explanation of the antonyms contained in them. surah of the Saba. The research method used is library research or literature study, and the data collected is in the form of secondary data such as scientific readings, scientific journals, research reports, Internet search results or through Internet sites, al-Qur'an Rasam Utsmani, and Ibn Katsir's commentary. According to Abdul Chaer, there are five types of antonyms, namely absolute antonyms, graded or stratified antonyms, relational or relational antonyms, hierarchical antonyms, and compound antonyms, meaning that an antonym has more than one pair. In contrast to Al-Khammas which has classified antonyms into five types, namely absolute antonyms (tadhad had), stratified antonyms (tadhad mutadarrij), opposite antonyms (tadhah aksiy), side-line antonyms (tadhad amudy), and straight line antonyms (tadhad imtidadi This article provides the results of the discussion that in the 54 verses of the Surah Saba there are three types of the five types of antonyms, namely absolute antonym (tadhad had), stratified antonym (tadhah mutadarrij), and straight line antonym (tadhad imtidadi). Research from the number of data for absolute antonyms is 11 words, 2-word-tiered antonyms, and 4-word straight line antonyms, so that the analysis results show that the total number of types of antonyms in Saba is 17 words with anonymity. There are various kinds of words found in this surah due to the inclusion of dhamir, the use of various sighah such as masdar, but they have i the same meaning when viewed from the root, then the word contradicts the meanings of other words which are termed antonyms.